Effects of catheter ablation on left atrial performance in different types of atrial fibrillation: a strain study. (25th November 2020) - Katbeh, A; De Potter, T; Geelen, P; Stefanidis, E; Iliodromitis, K; Barbato, E; Van Camp, G; Penicka, M
Abstract: Background: Atrial structural and functional changes may develop as a result of catheter ablation (CA) in patients with paroxysmal and persistent atrial fibrillation (AF). However, the relation between AF recurrence and atrial performance following CA is still under debate. Our aim is to describe the long-term effects of CA on LA remodeling and its correlates to the maintenance of sinus rhythm (SR). Methods: We prospectively enrolled 178 consecutive patients (age: 63±9 years, 35% females) with paroxysmal AF undergoing first-CA (67%) or redo-CA (22%), and 20 individuals (11%) with long-standing persistent AF (PAF) undergoing first CA. All patients underwent comprehensive transthoracic echocardiography at baseline and at 12-month follow-up, including the assessment of reservoir and contractile strain (LAS) using two dimensional speckle tracking echocardiography in all three apical views. The study population was divided in two sub-groups according to AF recurrence during follow-up. Results: During one-year follow-up, 144 (81%) patients maintained SR whereas 34 (19%) patients had AF recurrence [first-CA group 16 (13%), redo-CA group 8 (20%) and PAF group 10 (50%)]. Improvement of LAS was observed only in patients with paroxysmal and long-standing persistent AF who underwent the first CA and who remained in SR (Figure 1A, 1C). In contrast, recurrent AF was associated with absence of LAS improvement (Figure 1A, 1C). Different time course of LA performance was observed in the redo-CA group, i.e. LAS remained unchanged from baseline regardless of long-term maintenance of SR (Figure 1B). Moreover, at follow-up, no significant differences in LAS between redo-CA patients with SR versus AF were observed. Of note, in patients with long-standing persistent AF and SR, follow-up LAS increased to values observed in the redo-CA group. Conclusion: LA performance following CA is strongly affected by complex interplay between extent of atrial electro-structural remodeling and CA procedure. Repeated wide CA might affects negatively LA compliance and contractility despite SR restoration. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): International PhD programme in Cardiovascular Pathophysiology and Therapeutics (CardioPaTh).